Dynamics of Foliar Responses to O3 Stress as a Function of Phytotoxic O3 Dose in Hybrid Poplar - Turc, Benjamin; Vollenweider, Pierre; Le Thiec, Didier; Gandin, Anthony; Schaub, Marcus; Cabané, Mireille; Jolivet, Yves (Frontiers in Plant Science, 2021)
With background concentrations having reached phytotoxic levels during the last century, tropospheric ozone (O3) has become a key climate change agent, counteracting carbon sequestration by forest ecosystems. One of the main knowledge gaps for implementing the recent O3 flux-based critical levels (CLs) concerns the assessment of effective O3 dose leading to adverse effects in plants. In this study, we investigate the dynamics of physiological, structural, and morphological responses induced by two levels of O3 exposure (80 and 100 ppb) in the foliage of hybrid poplar, as a function of phytotoxic O3 dose (POD0) and foliar developmental stage. After a latency period driven by foliar ontological development, the gas exchanges and chlorophyll content decreased with higher POD0 monotonically. Hypersensitive response-like lesions appeared early during exposure and showed sigmoidal-like dynamics, varying according to leaf age. At current POD1_SPEC CL, notwithstanding the aforementioned reactions and initial visible injury to foliage, the treated poplars had still not shown any growth or biomass reduction. Hence, this study demonstrates the development of a complex syndrome of early reactions below the flux-based CL, with response dynamics closely determined by the foliar ontological stage and environmental conditions. General agreement with patterns observed in the field appears indicative of early O3 impacts on processes relevant, e.g., biodiversity ecosystem services before those of economic significance – i.e., wood production, as targeted by flux-based CL.